Vaccination-induced neutralizing antibodies in immunocompetent hosts correlate with protection against rickettsiae - Loka Reddy Velatooru; Jessica Plante; Chen Yi Chu; Garrett Cutchin; Bing Zhu; Nicole Burkhardt; Carsen Roach; Yingzi Cong; Shahid Karim; Yong-Fang Kuo; David H. Walker; Ulrike Munderloh; et al. (npj Vaccines)
Abstract We previously demonstrated that a single-dose immunization with a live-attenuated Rickettsia parkeri mutant 3A2 confers complete protection against murine spotted fever rickettsioses. In this study, we investigated whether vaccination-elicited serum antibodies serve as immune correlates of protection against rickettsiae. Immunization of immunocompetent C3H/HeN mice with 3A2 induced a robust and durable level of IgG antibody response, predominantly comprising IgG2a, IgG3, and IgG2b subclasses, and was associated with a significant expansion of CD19+ CD45R+ IgDlow plasma cells. Compared to mock controls, passive transfer of immune sera from 3A2-immunized mice protected C3H-SCID mice from R. parkeri challenge via multiple inoculation routes, including i.v., i.d. and i.d. plus tick saliva. Strikingly, serum antibodies of 3A2-immunized mice significantly reduced the number of R. parkeri plaques in vitro, indicating direct neutralizing activity. Collectively, our findings demonstrate that vaccination-induced serum IgG antibodies correlate with protection against rickettsial infection and possess direct neutralizing effects on rickettsiae.